2017
DOI: 10.1002/chem.201703946
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Composition‐Controlled Graphene‐Supported PtPd Alloy Nanocatalysts and Their Applications in Methanol Electro‐Oxidation and Lithium‐Oxygen Batteries

Abstract: A new and simple approach is reported for the synthesis of uniformly dispersed PtPd alloy nanocatalysts supported on graphene nanoplatelets (GNPs) (PtPd-GNPs) through the introduction of bifunctional materials, which can modify the GNP surface and simultaneously reduce metal ions. With the use of poly(4-styrenesulfonic acid), poly(vinyl pyrrolidone), poly(diallyldimethylammonium chloride), and poly(vinyl alcohol) as bifunctional materials, PtPd-GNPs can be produced through a procedure that is far simpler than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Then Pd-OH and Pt-CO could be reacted to release CO 2 and simultaneously regain the metal activity. [45,46] In addition, the mass activity of physically mixed PtPd NWs + graphene (520 mA mg À 1 metal ), PtPd/graphene-1 (727 mA mg À 1 metal ) and PtPd/graphene-2 (603 mA mg À 1 metal ) are less than PtPd NWs/ graphene, indicating that both synthesized process and Pt/Pd molar ratio could affect the morphology and MOR activity of the final products and PtPd NWs/graphene with optimized structure exhibits a superior MOR activity. When the graphene support is substituted by Vulcan XC-72R (labeled as PtPd/ carbon, Figure S9b), some PtPd NWs are loaded on the carbon, along with more agglomerated PtPd NWs.…”
Section: Resultsmentioning
confidence: 99%
“…Then Pd-OH and Pt-CO could be reacted to release CO 2 and simultaneously regain the metal activity. [45,46] In addition, the mass activity of physically mixed PtPd NWs + graphene (520 mA mg À 1 metal ), PtPd/graphene-1 (727 mA mg À 1 metal ) and PtPd/graphene-2 (603 mA mg À 1 metal ) are less than PtPd NWs/ graphene, indicating that both synthesized process and Pt/Pd molar ratio could affect the morphology and MOR activity of the final products and PtPd NWs/graphene with optimized structure exhibits a superior MOR activity. When the graphene support is substituted by Vulcan XC-72R (labeled as PtPd/ carbon, Figure S9b), some PtPd NWs are loaded on the carbon, along with more agglomerated PtPd NWs.…”
Section: Resultsmentioning
confidence: 99%
“…Second, different species of catalysts generate distinct battery performance . Because of their high reactivity, noble metals give rise to outstanding Li–O 2 battery performance, including the Pt, Pd, Au, and Ir. , As an additional bonus, their ability to suppress the formation of Li 2 CO 3 impurities can effectively extend the lifespan of Li–O 2 batteries. However, the high cost of noble metals still limits its application and alternatively boosts the interest of cost-effective alternatives for Li–O 2 batteries. In this regard, transition metal oxides have an unfilled 4d orbit and exhibit high reactivity as an electron donor and therefore can act as high catalytic candidates for Li–O 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Ye et al reported the preparation of alloyedP tPd NPs anchored on the surfaceo fg raphene. [42] The poisoning resistanceo fp alladium, combinedw ith the high electroactivity of platinum, resultedi n an enhanced electrochemical performance. An adequate ratio of Pt to Pd was stablished to be Pt 60 Pd 40 ,w hich resulted in a lower first cycle overpotential and the best cyclability (80 cycles at 200 mA g À1 to 1000 mAh g À1 )among different alloying ratios.…”
Section: Graphene-metal and Graphene-metal Oxide Compositesmentioning
confidence: 99%
“…Ye et al. reported the preparation of alloyed PtPd NPs anchored on the surface of graphene [42] . The poisoning resistance of palladium, combined with the high electroactivity of platinum, resulted in an enhanced electrochemical performance.…”
Section: Lithium–oxygen Batteriesmentioning
confidence: 99%